STRATEGI INVESTASI SAHAM PERBANKAN DENGAN PENDEKATAN TOP DOWN ANALYSIS - Prihatiningsih Prihatiningsih; Embun Duriany Soemarso; Mohammad Muslikh; Mochamad Abdul Kodir; Maharani Rona Makom (Politeknik Negeri Semarang, 2023)
Abstract : The population in this study are financial sector stocks listed on the Indonesian Stock Exchange, a sample of financial sector banking shares listed on the Indonesian stock exchange until December 2021. The analytical method used in this study is the Top Down Analysis method, which includes macroeconomic analysis, industry analysis. or sectoral analysis, analysis of financial statements or analysis of financial ratios, and analysis of stock valuations. Based on the results of macroeconomic analysis, Indonesia's average inflation rate of 2.73 in the last five years is relatively mild. The average BI Rate for the last five years has been 4.60%, with an average GDP of IDR 76,665.1 trillion, and the IHSG average for the last five years of 6,282.05. Based on these macro indicators, Indonesia in the last five years has been in a stable and conducive condition for investment. The growth of the Financial sector index exceeded the growth of the Jakarta Composite Index (IHSG). Based on the results of stock valuation and financial performance, banking stocks that have performed above the average for the financial sector in the last five years are shares of BBCA, BBRI, BBNI, BMRI, BBTN, and BDMN.